2017
DOI: 10.1080/14992027.2017.1370138
|View full text |Cite
|
Sign up to set email alerts
|

Using tablet-based technology to deliver time-efficient ototoxicity monitoring

Abstract: New mobile technology has the potential to influence the development and implementation of OMPs and lower barriers to patient access by providing time efficient, portable and self-administered testing options for use in the clinic and in the patient's home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 33 publications
(23 reference statements)
0
24
0
Order By: Relevance
“…The use of automated, portable systems in ototoxicity monitoring would allow for the possibility of other healthcare workers to be trained to administer a limited monitoring protocol under the supervision of an audiologist. 31 These devices could also allow for the patient to test himself or herself with results sent to the audiologist for interpretation. This is an area that would merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of automated, portable systems in ototoxicity monitoring would allow for the possibility of other healthcare workers to be trained to administer a limited monitoring protocol under the supervision of an audiologist. 31 These devices could also allow for the patient to test himself or herself with results sent to the audiologist for interpretation. This is an area that would merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Markov Model Schematic A tablet audiometer can be used to serve as a portable and accessible solution that can be used by health care professionals outside of the audiology department. 18 A previous study on the benefits of tablet-based ototoxicity monitoring for routine screening in adult CF patients showed that it increased patient accessibility and broadened the range of personnel capable of administrating screening. 19 Clinical pharmacists are uniquely positioned as the medication experts to conduct ototoxicity screening as a part of medication management and drug toxicity monitoring.…”
Section: Figurementioning
confidence: 99%
“…These applications generally rely on the internal sound card of the mobile device to process target media and a standard pair of headphones to present the sound to the user. While many of these applications have been developed and empirically researched as audiometers, few of these systems have the ability to administer general speech-in-noise tests (Brungart et al 2017). The ShoeBOX Audiometer system is an iPad-based hearing test system with support for testing with pure tones or speech stimuli (Rourke, Kong, and Bromwich 2016).…”
Section: Mobile Hearing Test Systemsmentioning
confidence: 99%